VIDEO “DOA UNTUK ORANG TUA” IN CHANNEL YOUTUBE - Rachmaniar Rachmaniar (Metakom, 2019)
The purpose of this study was to analyze the response of netizens is related video “Doauntuk Orang Tua” on youtube channel Kastari Animation Official.The method used in this research is qualitative method with virtual ethnography approach to analyze the existence video “Doauntuk Orang Tua” on youtube channel Kastari Animation Official. The main objects of this research is the video “Doa untuk Orang Tua” on youtube channel KastariAnimation Official. The technique of collecting data through participant observation and study of literature. These results indicate that the response of netizens related the video “Doauntuk Orang Tua” on youtube channel Kastari Animation Official are: 1) many netizens who gave positive remarks concerning the video, 2) there are netizens who give negative comments concerning the video, and 3) there are netizens who express some request related to the uploaded video. Keywords: video, youtube, virtual ethnography